Sosialisasi Pendidikan Tinggi dan Penerimaan Mahasiswa Baru Institut Teknologi Alberth Foenay dalam Meningkatkan Minat Siswa SMA Melanjutkan Studi ke Perguruan Tinggi - Stefanus Neno; Betheldo R. Foenay; Herlan P. S. Basharie (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Introducing higher education institutions and promoting new student admissions are strategic efforts to enhance youth participation in pursuing advanced education. The Institut Teknologi Alberth Foenay (ITAF), as a tertiary institution committed to advancing science and technology, has implemented outreach programs aimed at presenting its vision, mission, academic programs namely Mechanical Engineering, Environmental Engineering, and Informatics and its supporting facilities to prospective students. This study aims to describe the implementation of ITAF 2026 student admission outreach activities and assess their effectiveness in enhancing students' awareness and interest in higher education. This community engagement initiative adopts a qualitative descriptive approach, employing data collection methods such as direct observation, in-depth interviews, and documentation of outreach activities conducted in various high schools. The findings indicate that both in-person and digital outreach activities significantly improved prospective students’ understanding of ITAF and influenced their decision-making processes in selecting a university. These results highlight the crucial role of well-planned and consistent communication strategies in the student recruitment process.